محمد سلیم الرحمٰن کی پنجابی نظمیں: ANALYSIS OF MUHAMMAD SALIM-UR-RAHMAN'S PUNJABI POEMS (Al-Aasar, 2025)
Muhammad Salim-ur-Rahman’s three Punjabi poems, as presented in the collection Nazmain, encapsulate profound themes through simple yet evocative language, reflecting an urbanized Punjabi diction familiar to city dwellers. The first poem explores the existential bewilderment of individuals trapped in an incomprehensible world, grappling with an unreadable fate that shapes their lives. The second poem delves into the poet’s introspective astonishment at the subtle light hidden within his heart, a mystery illuminated during the quiet of the night. The third poem offers a hopeful vision, envisioning a realm beyond sleep where lost connections and past joys might be reclaimed. Together, these poems weave a tapestry of human longing, destiny, and the search for meaning, using a straightforward yet poignant style. They reflect the poet’s deep connection to Punjab, particularly Lahore, and his ability to convey universal human experiences through a regional lens. The poems’ simplicity belies their depth, inviting readers to reflect on life’s mysteries, the weight of fate, and the solace found in dreams and memories.